Has the phasing out of stavudine in accordance with changes in WHO guidelines led to a decrease in single-drug substitutions in first-line antiretroviral therapy for HIV in sub-Saharan Africa?. (2nd January 2017) - Brennan, Alana T.; Davies, Mary-Ann; Bor, Jacob; Wandeler, Gilles; Stinson, Kathryn; Wood, Robin; Prozesky, Hans; Tanser, Frank; Fatti, Geoffrey; Boulle, Andrew; Sikazwe, Izukanji; Wools-Kaloustian, Kara; et al.
Abstract : Objective: We assessed the relationship between phasing out stavudine in first-line antiretroviral therapy (ART) in accordance with WHO 2010 policy and single-drug substitutions (SDS) (substituting the nucleoside reverse transcriptase inhibitor in first-line ART) in sub-Saharan Africa. Design: Prospective cohort analysis (International epidemiological Databases to Evaluate AIDS-Multiregional) including ART-naive, HIV-infected patients aged at least 16 years, initiating ART between January 2005 and December 2012. Before April 2010 (July 2007 in Zambia) national guidelines called for patients to initiate stavudine-based or zidovudine-based regimen, whereas thereafter tenofovir or zidovudine replaced stavudine in first-line ART. Methods: We evaluated the frequency of stavudine use and SDS by calendar year 2004–2014. Competing risk regression was used to assess the association between nucleoside reverse transcriptase inhibitor use and SDS in the first 24 months on ART. Results: In all, 33 441 (8.9%; 95% confience interval 8.7–8.9%) SDS occurred among 377 656 patients in the first 24 months on ART, close to 40% of which were amongst patients on stavudine. The decrease in SDS corresponded with the phasing out of stavudine. Competing risks regression models showed that patients on tenofovir were 20–95% less likely to require a SDS than patients on stavudine, whereas patients on zidovudine had a 75–85% decrease in the hazards of SDS when compared to stavudine. Conclusion: The decline in SDS in the first 24 months on treatment appears to be associated with phasing out stavudine for zidovudine or tenofovir in first-line ART in our study. Further efforts to decrease the cost of tenofovir and zidovudine for use in this setting is warranted to substitute all patients still receiving stavudine. Abstract : Supplemental Digital Content is available in the text